OPTIMIZING THE RATIO OF AEROBIC AND ANAEROBIC LOADS IN TRAINING MIDDLE- AND LONG-DISTANCE RUNNERS, CONSIDERING SOMATOTYPOLOGICAL CHARACTERISTICS - Bekmurzaev, Abdikarim Kulmurzaevich (SCIENCE and SOCIETY, 2026)
The purpose of the study is to determine the effectiveness of individualized distribution of aerobic and anaerobic loads in middle and long-distance runners, taking into account the somatotypes. 36 athletes participated in the study, divided into control and experimental groups. The experimental methodology provided for differentiated planning of loads depending on the morphofunctional characteristics of the athletes. Functional testing VO 2max, lactate test, heart rate monitoring, and test distances were used. The results showed a significant improvement in aerobic and anaerobic indicators, a decrease in lactate concentration, and an increase in sports results in the experimental group. The methodology demonstrates high effectiveness and can be applied in the runner training system.
Keywords: aerobic loads; anaerobic loads; medium and long-distance running; somatotype; VO2max; lactate; individualization of the training process